The talented clementine eaudiobook - Pennypacker, Sara (Clementine, 2007)
This delightful New York Times bestselling chapter book series, from the award-winning author of Pax , is a modern classic that has been keeping readers engaged and laughing as they follow the hijinks of Clementine, a clever and quirky third grader who's the most spectacular friend around. Perfect for fans of Amelia Bedelia and Ivy + Bean! When it comes to tackling third grade, Clementine is at the top of her game—okay, so maybe not all the time. After her teacher announces that the third and fourth graders will be putting on a talent show, Clementine panics. She doesn't sing or dance or play an instrument. She can't even hop with finesse. And as if that didn't make her feel bad enough, her perfect best friend, Margaret, has so many talents, she has to alphabetize them to keep them straight? How can Clementine ever hope to compete? As the night of the big "Talent-palooza" draws closer, Clementine is desperate for an act, any act. But the unexpected talent she demonstrates at the show surprises everyone—most of all herself.